Teachers’ Perspectives and Experiences in Higher Education Vocabulary Instruction - Tantri, Ni Nyoman; Padmadewi, Ni Nyoman; Artini, Luh Putu (The Study Program of English Education of Palangka Raya University, 2025)
The selection of vocabulary learning strategies (VLS) is a pivotal action in the English teaching and learning process. This study aimed to explore what teachers perceive and experience in vocabulary instruction in higher education. A narrative approach was employed in this study. Using the purposive sampling technique under the criteria of a minimum of four years of experience as permanent English teachers and limited the area of study only to one of religious higher education in Central Kalimantan, five English teachers were enrolled as participants. Unstructured, open-ended interviews were used as the instrument for collecting the primary data. After collecting the stories, the data were reported and validated using triangulation. The results revealed that teachers believed that using a variety of learning strategies to engage learners to be interested in vocabulary instruction was useful. Then, the challenges both external and internal factors faced by teachers in vocabulary instruction could be handled by employing the strategies that fit the students’ characteristics, such as learning vocabulary through songs, games, and social media platforms such as TikTok, YouTube, Instagram, and so forth. Therefore, it can be drawn to the conclusion that teachers must always be creative and innovative in action by utilizing technology advancement. Besides, the use of differentiated instruction approach could be better employed by teachers for solutions to problems, particularly in facilitating diverse student characteristics. Next, the use of various modes of learning or multimodal sources can also help students in higher education to get very meaningful vocabulary learning.